Population genetic analyses of Helicobacter pylori isolates from Gambian adults and children. - Ousman Secka; Yoshan Moodley; Martin Antonio; Douglas E Berg; Mary Tapgun; Robert Walton; Archibald Worwui; Vivat Thomas; Tumani Corrah; Julian E Thomas; Richard A Adegbola (PLoS ONE)
The gastric pathogen Helicobacter pylori is one of the most genetically diverse of bacterial species. Much of its diversity stems from frequent mutation and recombination, preferential transmission within families and local communities, and selection during persistent gastric mucosal infection. MLST of seven housekeeping genes had identified multiple distinct H. pylori populations, including three from Africa: hpNEAfrica, hpAfrica1 and hpAfrica2, which consists of three subpopulations (hspWAfrica, hspCAfrica and hspSAfrica). Most detailed H. pylori population analyses have used strains from non-African countries, despite Africa's high importance in the emergence and evolution of humans and their pathogens. Our concatenated sequences from seven H. pylori housekeeping genes from 44 Gambian patients (MLST) identified 42 distinct sequence types (or haplotypes), and no clustering with age or disease. STRUCTURE analysis of the sequence data indicated that Gambian H. pylori strains belong to the hspWAfrica subpopulation of hpAfrica1, in accord with Gambia's West African location. Despite Gambia's history of invasion and colonisation by Europeans and North Africans during the last millennium, no traces of Ancestral Europe1 (AE1) population carried by those people were found. Instead, admixture of 17% from Ancestral Europe2 (AE2) was detected in Gambian strains; this population predominates in Nilo-Saharan speakers of North-East Africa, and might have been derived from admixture of hpNEAfrica strains these people carried when they migrated across the Sahara during the Holocene humid period 6,000-9,000 years ago. Alternatively, shared AE2 ancestry might have resulted from shared ancestral polymorphisms already present in the common ancestor of sister populations hpAfrica1 and hpNEAfrica.